2020
DOI: 10.3389/fcell.2020.539485
|View full text |Cite
|
Sign up to set email alerts
|

AMPK Activity Contributes to G2 Arrest and DNA Damage Decrease via p53/p21 Pathways in Oxidatively Damaged Mouse Zygotes

Abstract: Oxidatively-Stressed Mouse Zygote Cell-Cycle Regulation facilitating the repair of DNA damage and the development and survival of oxidative stress-damaged embryos. Our study provides insights into the molecular mechanisms underlying oxidative-stress induced embryonic developmental arrest, which is crucial for the development of novel strategies to ensure viable embryo generation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
19
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(20 citation statements)
references
References 68 publications
1
19
0
Order By: Relevance
“…After adding AMPK inhibitor, there was a reversal in G2 phase arrest in mouse fertilized eggs, the rate of blastocysts apoptosis was increased, and the formation rates of four‐cell embryos and blastocysts were decreased. [ 96 ] In summary, evidences indicate that AMPK activation arrests cell cycle and inhibit proliferation of cancer cells.…”
Section: Regulation Mechanisms Of Ampkmentioning
confidence: 99%
See 1 more Smart Citation
“…After adding AMPK inhibitor, there was a reversal in G2 phase arrest in mouse fertilized eggs, the rate of blastocysts apoptosis was increased, and the formation rates of four‐cell embryos and blastocysts were decreased. [ 96 ] In summary, evidences indicate that AMPK activation arrests cell cycle and inhibit proliferation of cancer cells.…”
Section: Regulation Mechanisms Of Ampkmentioning
confidence: 99%
“…AMPK is an important gene that regulates the transport of cell energy and controls cell cycle and growth. [ 97 ] It is easy to associate its function with the characteristics of cancer cells. As a tumor suppressor gene, LKB1 can regulate AMPK and at least 12 downstream kinases related to AMPK, [ 75 ] suggesting that AMPK may play an important role in suppressing tumors.…”
Section: The Relationship Between Ampk Activation and Carcinogenesismentioning
confidence: 99%
“…We detected the mitochondria membrane potential at 5 hpa, ROS level at 9 hpa and γ-H2A.X at 12 hpa in zygotes, respectively and found that oocyte vitrification decreased the mitochondrial activity and increased ROS production and DNA damage, however, these damages were considerably alleviated by MT treatment, potentially promoting the cleavage rates. The oocyte vitrification-inflicted oxidative stress might delay or arrest the G2/M phase transition via activating ATM/Chk1 [49] or AMPK-p53/p21 [60] pathway, partially leading to delay or arrest of cleavage. It has been reported that MT is a powerful scavenger of ROS and can maintain the genome integrity [62].…”
Section: Discussionmentioning
confidence: 99%
“…It seems that the oxidative stress-induced DNA damage can activate the ATM/Chk1 and phosphorylate Cdc25 and Cdc2, which can further trigger G2/M arrest of zygote [ 49 ]. Furthermore, the oxidative stress-induced phosphorylation and activation of AMPK can inhibit CDK1 activity via p53/p21 pathways, thereby delaying the G2/M phase transition and facilitating the repair of DNA damage in zygotes [ 60 ]. Previously Lei and colleagues have shown that vitrification-inflicted mitochondrial oxidative damage can lead to the reduced developmental potential in vitrified mouse oocytes [ 61 ].…”
Section: Discussionmentioning
confidence: 99%
“…This situation is reflected in this study where different genes related to oxidative stress were upregulated in IVP embryos, including essential genes involved in the protection of cells against free radicals such as GSS , GPX4 , GSTA , MGST1 [ 67 ], TXN , TXNIP , NXN [ 68 ], SOD1 [ 69 ] and SESN1 [ 70 ]. One of the main consequences of this overexposure to different types of free radicals is the damage that they cause to DNA [ 71 ], which has been confirmed in both oocytes [ 72 ] and embryos [ 73 , 74 , 75 ]. In that sense, in this study, we observed how, independent of the culture type, IVP embryos overexpressed genes involved in DNA repair processes.…”
Section: Discussionmentioning
confidence: 99%